Optics of the ozone lidar ELSA - Porteneuve, J. (1992)
In order to study the ozone layer in the Arctic, we have to define a new optical concept for a lidar. It was necessary to build a transportable system with a large collecting surface in a minimum of volume. It was too useful to have a multichannel receptor. A description of the Emettor Receptor System, collecting system, and analysis system is provided.